Activating Controlling Images in the Racialized Interaction Order: Black Middle‐Class Interactions and the Creativity of Racist Action. Issue 2 (17th October 2018) - Meghji, Ali
Abstract : This paper investigates the link between the racial hierarchy and the racialized interaction order, questioning how controlling images of blackness are mediated in interactions. I explore this through interviews with thirty‐two black British middle‐class individuals, examining their interactions in the professional workplace. I argue that white people often draw on a practical knowledge of "white ignorance" to activate controlling images in their interactions with black professionals. This white ignorance allows for white people to find creative ways to irrationally deploy controlling images, and to adapt controlling images to specific interactional settings.